Historiographical Aspect of Investigating the Problem of Training National Teachers of Foreign Language - Misechko, Olha (Pedagogical Discourse, 2013)
The article suggests author’s systematization of historical works that touch upon the problem of development of specialized professional preparation of national teachers of foreign languages (Classics and modern). The systematization is based on the crossroad of problem/topic-centered and chronological approaches. According to the problem/topic-centered approach, the body of historical-pedagogical researches is divided into three groups: 1) those that cover the process of introduction and dissemination of foreign language teaching; 2) those that deal with the historical development of the higher pedagogical education in Ukraine; 3) those that study the gradual growth of organizational background, content and forms of professional preparation of language teachers. According to the chronological principle, four historiographical periods have been singled out: I – second half of the ХІХ c. – 1917; II – 1917 ‒19 20s; III – 1930s –1980s; IV –1990s –begin. of the ХІХ с.